Buprenorphine exposures in adolescents and adults: a 10‐year experience of a French Poison Control Center. (16th December 2020) - Boulamery, Audrey; von Fabeck, Katharina; Glaizal, Mathieu; de Haro, Luc; Simon, Nicolas
Abstract: Buprenorphine has been used in pain and opioid addiction management for nearly 25 years. Compared to methadone, buprenorphine is thought to exhibit less side effects and respiratory depression in case of accidental or suicidal overdose. The aim was to describe the characteristics of exposures reported to a French Poison Control Center (PCC). We conducted a retrospective study including all buprenorphine exposures for which advice of our PCC was required between 2009 and 2018. After data extraction from the electronic medical files and anonymous transfer to an Access base, a statistical descriptive analysis was performed focusing on adolescents over 10 years old and adults. One hundred and ninety‐nine cases were analyzed. The major circumstances of exposure were suicide attempts and overdoses in patients with previously identified substance abuse. Buprenorphine exposures have been reduced by 50% between 2009 and 2018. Coingestions, often with benzodiazepines or antidepressants, were almost systematic and 79% of all the series exhibited at least one symptom. Among the symptomatic cases, neurological effects were the most frequent (83%) and respiratory symptoms occurred in 13%. No deaths were registered. Severity did not exceed PSS1 in 80% of all the cases. Treatment was mainly symptomatic even though naloxone was required in at least 5% of the symptomatic cases. Within 24 h after exposure, 120 patients were discharged from the emergency department. Despite loss to follow‐up, our results suggest that buprenorphine is relatively safe.